(untitled) (Bangladesh Journal of Botany, 2023)
Purple blotch (Alternaria porri) is one of the major diseases of garlic causing huge loss to the growers. An investigation was undertaken to formulate suitable management practices against purple blotch of garlic var. DWG1. Among the various treatments, seed treatment with Trichoderma harzianum @ 10 g/kg of cloves and two foliar applications of fluopyram 17.7% + tebuconazole 17.7% @ 0.1% on 50 and 65 days after sowing recorded the minimum disease severity (13.34 PDI) and higher bulb yield (5.77 t/ha), 10 bulbs weight (83.00 g), number of cloves (15.67) and 100 cloves weight (65.33 g) with C:B ratio of 1: 3.51. The combined application of cow urine, nimbecidine and Trichoderma harzianum also showed significant impact on disease reduction as well as on yield of garlic. However, fluopyram 17.7% + tebuconazole 17.7% showed a higher benefit with minimum production cost and this approach is proposed to garlic growing farmers to mitigate the purple blotch disease. Bangladesh J. Bot. 52(2): 291-295, 2023 (June)